HANDICRAFTS FROM RATTAN AS A CREATIVE AND INNOVATIVE EFFORT FOR STKIP SINGKAWANG STUDENTS - Rika Wahyuni; Ayu Indriani; Fransiska Ancis; Friska Willasari; Uley Lin (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2020)
This study aims to develop students' interest and creativity in opening business opportunities that can increase experience, motivate them to develop innovations and creations. One of them is by using rattan. Rattan is a group of palms from the tribe (tribus) Calameae which has a climbing habitus, especially Calamus, Daemonorops, and Oncocalamus. Rattan grows wild in the forest or is planted intentionally. Rattan can be harvested at any time, with the attention that the bottom of the stem is not covered by petals, the leaves have dried, the thorns and petals have fallen off. Masaih rattan is easy to find in our area. Therefore we have the initiative to make handicrafts or items that are useful and value for sale. So, we STKIP Singkawang students innovate to make a study of rattan. In addition, to add to the attractiveness and selling value, we also add various forms so that buyers are more interested and for the price problem offered also according to the shape and size of the goods being produced. To market this product we sell it directly and through social media.